Rolul Curţii Europene a Drepturilor Omului în mecanismul de protecţie împotriva inacţiunilor autorităţilor publice din Republica Moldova [Articol] - Boico, Mariana (Institutul Naţional al Justiţiei, 2019)
Autorul analizează posibilităţile de depăşire a unor inacţiuni ale autorităţilor statului în soluţionarea problemei sistemice („structurale”), care prezintă motivul pentru adresare la Curtea Europeană a Drepturilor Omului în chestiuni similare. Se efectuează o analiză a mecanismul de identificare a „problemelor sistemice” şi se oferă o analiză a implementării practice a meto- dologiei hotărârilor-pilot, care obligă statele membre să ia măsuri pentru rezolvarea acestor probleme. Sunt cercetate sarcinile CtEDO, folosind procedura de hotă- râre-pilot, precum şi cadrul legal care defineşte mecanismul şi consecinţele adoptării hotărârilor-pilot.

The paper analyzes the ECHR case practice on the efficiency of the body to implement the right of Moldavian citizens to enforce the enacted court decisions as a constitutional guarantee of judicial protection. The objective of the paperis analyzing the possibilities to overcome the non-feasance of Republic of Moldova authorities on solving this system problem serving a basis to address the ECHR on similar cases. The author researches the mechanism of identifying structural issues and analyzes the implementation of the methods of pilot judgements which obliged states to take measures to solve the problems. The research concerns the ECHR tasks to use the procedure of pilot judgements and legal framework determining the mechanism and consequences of taking pilot judgements. The analysis also concerns the causes determining the application of such judge- ments by the ECHR with the majour one being li- mited resources and possibilities of the ECHR in the condition of the growing number of individual complaints.
The role of the European Court of Human Rights in the protection mechanism against the inactions of public authorities of the Republic of Moldova
Keywords: drept internaţional; Curtea Europeană a Drepturilor Omului; dreptul constituțional la apărare; reptul la executarea hotărârilor judecătoreşti; Convenția pentru protecția drepturilor omului şi libertățile fundamentale; ECHR; constitutional right to judicial protection; right to implementing final and binding court decision; European Convention on Human Rights